Carfilzomib and dexamethasone induction with lenalidomide, clarithromycin and dexamethasone consolidation and lenalidomide maintenance for newly diagnosed multiple myeloma. Issue 12 (4th September 2021) - Forsberg, Peter A.; Rossi, Adriana C.; Boyer, Angelique; Pearse, Roger N.; Pekle, Karen A.; Jayabalan, David; Lakritz, Stephanie; Flicker, Kari; Ribadeneyra, Drew; Liotta, Brielle; Ely, Scott; Boussi, Leora; et al.
Abstract: Combination treatment regimens including a proteasome inhibitor (PI), an immunomodulatory agent (IMiD) and a corticosteroid are standards of care for initial treatment of multiple myeloma (MM). We aimed to evaluate if a sequential treatment program using PI induction followed by IMiD based consolidation and maintenance could achieve similar outcomes with reduced toxicities. This phase 2 study was designed to assess the safety and efficacy of the Car‐BiRd regimen: carfilzomib and dexamethasone (Kd) induction until maximum response, followed by lenalidomide, clarithromycin and dexamethasone (BiRd) consolidation until next maximum response, then lenalidomide maintenance in patients with newly diagnosed MM. Seventy‐two patients, including both transplant eligible and ineligible patients, were enrolled and evaluated for response. The overall response rate to the Car‐BiRd regimen was 94% with 83% of patients achieving a ≥ VGPR and 35% achieving a CR/sCR. The rate of CR/sCR increased from 7% with Kd induction to 21% with BiRd consolidation and 35% with lenalidomide maintenance. These results did not meet the study's target endpoint of a CR rate of 55%. The median PFS using this deferred transplant approach was 37.3 months (95% CI 27.9, 52.7) and median OS was not reached with a median follow‐up of 60 months. Toxicities were primarily low grade and manageable. Hematologic toxicities were lower than those expected with a combination PI/IMiD protocol. The sequential Car‐BiRd regimen is an effective and safe approach for the upfront treatment of MM including patients unfit for transplant.